Age differences in moral judgment: Older adults are more deontological than younger adults. (19th June 2018) - McNair, Simon; Okan, Yasmina; Hadjichristidis, Constantinos; de Bruin, Wändi Bruine
Abstract: In 2 studies, an older and a younger age group morally evaluated dilemmas contrasting a deontological judgment (do not harm others) against a utilitarian judgment (do what is best for the majority). Previous research suggests that deontological moral judgments are often underpinned by affective reactions and utilitarian moral judgments by deliberative thinking. Separately, research on the psychology of aging has shown that affect plays a more prominent role in the judgments and decision making of older (vs. younger) adults. Yet age remains a largely overlooked factor in moral judgment research. Here, we therefore investigated whether older adults would make more deontological judgments on the basis of experiencing different affective reactions to moral dilemmas as compared with younger adults. Results from 2 experiments indicated that older adults made significantly more deontological moral judgments. Mediation analyses revealed that the relationship between age and making more deontological moral judgments is partly explained by older adults exhibiting significantly more negative affective reactions and having more morally idealistic beliefs as compared with younger adults.